6y2=36

Divide each term in 6y2=36 by 6.

6y26=366

Cancel the common factor of 6.

Cancel the common factor.

6y26=366

Divide y2 by 1.

y2=366

y2=366

Divide 36 by 6.

y2=6

y2=6

Take the square root of both sides of the equation to eliminate the exponent on the left side.

y=±6

First, use the positive value of the ± to find the first solution.

y=6

Next, use the negative value of the ± to find the second solution.

y=-6

The complete solution is the result of both the positive and negative portions of the solution.

y=6,-6

y=6,-6

The result can be shown in multiple forms.

Exact Form:

y=6,-6

Decimal Form:

y=2.44948974…,-2.44948974…

Solve Using the Square Root Property 6y^2=36